2019
DOI: 10.1017/s0007114519003325
|View full text |Cite
|
Sign up to set email alerts
|

Trans-10,cis-12 conjugated linoleic acid reduces milk fat content and lipogenic gene expression in the mammary gland of sows without altering litter performance

Abstract: Trans-10, cis-12 conjugated linoleic acid (CLA) decreases milk fat synthesis in lactating sows and involves, at least in part, the down-regulation of lipogenic genes. The objective was to evaluate the effect of CLA on milk composition and lipogenic gene expression. Twenty multiparous sows were randomly assigned to one of the two treatments for 18 d (from day 7 to day 25 of lactation): (1) control (no CLA added) and (2) 1 % of CLA mixed into the ration. CLA treatment decreased milk fat and protein content by 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The significant covariates do not necessarily indicate a cause–effect relationship with the response variable; instead, they may have a relationship with other variables (latent variables) that indeed affect milk fat metabolism. For instance, CLA has been shown to downregulate the gene expression of regulatory enzymes in the de novo FA synthesis pathway (Bauman et al, 2008; Sandri et al, 2020; Ticiani et al, 2016). Therefore, the products of that metabolic pathway (i.e., SCFA and MCFA) may be significant predictors in models that estimate milk fat without direct affecting the response variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant covariates do not necessarily indicate a cause–effect relationship with the response variable; instead, they may have a relationship with other variables (latent variables) that indeed affect milk fat metabolism. For instance, CLA has been shown to downregulate the gene expression of regulatory enzymes in the de novo FA synthesis pathway (Bauman et al, 2008; Sandri et al, 2020; Ticiani et al, 2016). Therefore, the products of that metabolic pathway (i.e., SCFA and MCFA) may be significant predictors in models that estimate milk fat without direct affecting the response variable.…”
Section: Discussionmentioning
confidence: 99%
“…Other FA were included in three of the four regressions tested: c9, c12, c15‐18:3; c9‐18:1; 16:0; 6:0 and 4:0. The SCFA and MCFA are products of the de novo FA synthesis and this pathway may be inhibited by trans ‐10 FA (Bauman et al, 2008; Sandri et al, 2020; Ticiani et al, 2016), 16:0 (Carraro et al, 2019; Tian et al, 2017) and PUFA (Sampath & Ntambi, 2004; Toral et al, 2015). In addition, c9‐18:1 has been negatively related to the SCD gene in cows (Keating et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most predominant biologically active isomers in natural CLA are "c9, t11" CLA, and "t10, c12" CLA (Giordano et al, 2011). Previous studies have shown that natural CLA has the potential to reduce body fat (Sandri et al, 2020) and cholesterol (O'Reilly et al, 2020;Yeonhwa Park et al, 2010), and enhances immunity (Park et al, 2008). In addition to being the essential fatty acid for human, CLA is also the material for synthesizing some structured lipids (Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of milk fat synthesis by the administration of trans-10, cis-12 CLA is mediated, at least in part, by down-regulating the gene expression of lipogenic enzymes and transcription factors in the mammary gland. Such effects have been demonstrated in several species of domestic animals, such as cows (8) , sheep (9) , goats (10) and sows (11) .…”
mentioning
confidence: 99%